Programa de gestión para reducir la tasa de desactivaciones corporativas por portabilidad en Entel Perú - Magill Ramírez, Alexandra (2021)
This work was based on the analysis of a well-known company within the Peruvian telecommunications industry: Entel Peru. The center of the study was the corporate client segment. It is known that this segment represents just over a third of the company's postpaid base and is responsible on average for about 15% of the business movement. The purpose of the research was to reduce the rate of corporate deactivations due to portability and it sought to test the hypothesis that coverage, price, service quality and relationship are the factors that are significantly associated with the migration of corporate clients from the company. To carry out this study, a population of 2,923 corporate clients of the Entel Peru company was used as the unit of analysis. Regarding the results of the study, it was possible to demonstrate the hypothesis formulated at the level of variable migration. Stating that it is influenced by the four factors mentioned, being the quality of the service the one with the highest incidence.